ASSESING NUTRIENT SUSTAINABILITY OF FOREST PRODUCTION FOR DIFFERENT TREE SPECIES CONSIDERING CA, MG, K, N AND P AT BJöRNSTORP ESTATE, SWEDEN - Sverdrup H.; Thelin G.; Robles M.; Stjernquist I.; Sörensen J. (My University, 2006)
An assessment of nutrient sustainability has been done for stands of European beech, Sycamore maple, European oak, Norway spruce, Larch, Grandis fir and Douglas fir at Björnstorp Estate in southern Sweden. To estimate the nutrient sustainability, mass balance was calculated with respect to Ca, Mg, K, N and P. The release from mineral weathering was calculated using the PROFILE model. The leaching has been estimated from observed soil water concentrations and nutrients removed by harvest from projected production. The results indicate that the planned production is on the limits of sustainability and sometimes in excess of it. The stands will overuse Ca, sometimes also Mg, K and P, if all growth is harvested. Soil acidification is still progessing at Björnstorp Estate, and soil depletion is the result of this. The estimated sustainable yield and the mass balances suggest that the leaching rate is the most uncertain factor for assessing sustainability. Different types of critical loads were investigated, including a new type, based on no excess acidity in the system. The calculations stress the importance of reducing the acid deposition and that nutrient sustainable management must be included in forest management. © 2006 Springer Science+Business Media, Inc.
Keywords: ACIDIFICATION; DOUGLAS FIR; EUROPEAN BEECH; EUROPEAN LARCH; EUROPEAN OAK; FOREST PRODUCTION; GRANDIS FIR; NORWAY SPRUCE; NUTRIENTS; SUSTAINABILITY; SYCAMORE MAPLE